Mengurangi Penyebab Plagiat pada Tugas Akhir Semester Melalui Bimbingan Kelompok Mahasiswa BK Universitas Muslim Nusantara Alwashliyah - Dina Hidayati Hutasuhut; Muhammad Noer Fadlan; Dinda Yarshal (Departement of Mathematics Education, 2023)
This study aims to find out the description of the causes of plagiarism in the final semester assignments carried out by guidance and counseling students. Plagiarism behavior is imitating, imitating, quoting writings, work or other people's work either intentionally or unintentionally in completing exam assignments or making papers without including proper and adequate sources to obtain learning grades. The method used is an observational and qualitative approach. The sample in this study were students in the 5th semester of counseling guidance, totaling 6 students from the Muslim Nusantara Alwashliyah University. Verbatim dialogue and questionnaire results show that from observations before cycle I to cycle II there has been an increase in reducing the habit of plagiarism.